2002
DOI: 10.1053/seiz.2002.0684
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of epilepsy amongst school children in Izmir, Turkey

Abstract: The prevalence of epilepsy is higher in school-age children in Izmir province compared to that in developed countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
4
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 31 publications
3
24
4
6
Order By: Relevance
“…The average prevalence rate in 32 studies from different parts of the world has been estimated at 5.16/1000 [23]. In Pakistan, 11.1 (an average in urban and rural areas) [14], While some studies reported 9.8 [15,24] There were so many studies that did not show any significant gender difference [26],But most of the surveys show high prevalence percentages in male; which is assumed to reflect the contribution of etiologic factors such as head trauma known to be more frequent in males [12,27]. Similarly high prevalence percentage in female at primary (60.7%) and secondary (35.7); while these percentages were higher at tertiary and professional level in male population; 20.9% and 12.8% respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The average prevalence rate in 32 studies from different parts of the world has been estimated at 5.16/1000 [23]. In Pakistan, 11.1 (an average in urban and rural areas) [14], While some studies reported 9.8 [15,24] There were so many studies that did not show any significant gender difference [26],But most of the surveys show high prevalence percentages in male; which is assumed to reflect the contribution of etiologic factors such as head trauma known to be more frequent in males [12,27]. Similarly high prevalence percentage in female at primary (60.7%) and secondary (35.7); while these percentages were higher at tertiary and professional level in male population; 20.9% and 12.8% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly high prevalence percentage in female at primary (60.7%) and secondary (35.7); while these percentages were higher at tertiary and professional level in male population; 20.9% and 12.8% respectively. It is possible that epilepsy in women was underreported due to various social and cultural factors [28], which need to be explored especially in this male dominant hard area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[17][18][19][20][21][22][23][24] According to this, considering that approximately 700,000 epilepsy patients exist in Turkey, about 10% of this epilepsy population is surgery candidates. The benefits of epilepsy surgery in terms of seizure outcome and improvements in life quality are beyond controversy in well selected patient groups, especially in temporal lobe epilepsy with hippocampal sclerosis.…”
Section: Discussionmentioning
confidence: 99%